Desenvolvimento e avaliação de jogo educativo para cegos : acesso à informação sobre o uso de drogas psicoativas - Mariano, Monaliza Ribeiro (2010)
Nursing uses different strategies and technologies to insert blind people in the health promotion context. As these predominantly use paper and ink, illustrations and/or television images, programs to prevent and combat drugs limit blind clients’ information access. Feasible technologies for health promotion include Assistive Technology (AT). Games adapted to the blind represent a different education possibility, associating the playful with information collection and, hence, with knowledge, so that they are considered an Assistive Technology and contribute to awareness-raising on the theme, collaborating to turn health promotion into permanent education. Thus, the goal was the development of an Assistive Technology in the form of an educational game on psychoactive drugs use, accessible to the blind, and the assessment of this technology by special education specialists and blind people. An assistive technology construction and assessment study was carried out between June and August 2010 at the Health Communication Laboratory of the Federal University of Ceará (LabCom_Saúde-UFC). Study participants were three special education specialists and twelve blind people. The research involved three methodological phases: construction of the educational game, assessment by special education specialists and assessment by the blind. For assessment purposes, an instrument was elaborated in the form of a Likert scale. Items were divided into adequate, partially adequate, inadequate and does not apply. The three specialists assessed the first version of the assistive technology, Version Alpha, and made suggestions, which were accepted when pertinent. After the adjustments, the specialists assessed the second version of the game, Version Beta, until no further adjustments were needed. Next, three pairs of blind people played the game and assessed Version Beta and, thus, made suggestions, which were incorporated when pertinent. The last three pairs of blind people assessed the new version of the game, Version Gamma. The evaluation phase by the blind people was filmed to facilitate data collection. All study participants signed the Free and Informed Consent Term. Version Alpha was presented to the specialists, who formulated suggestions on the dimension of the board, aspects related to the texture of the board spaces, game pawns, such as the distinction among the pawns, quality of Braille writing and description of the game instructions. After the adjustments, version Beta was constructed and again assessed by the specialists, who considered it adequate. Next, the blind participants’ assessed the game, appointed aspects related to the texture of the spaces and suggested using Velcro in each space to fix the pawn during the moves. After making the adjustments, the assessment continued with the last three pairs, who considered the AT adequate. The participants’ interest and curiosity in the game was evidenced, besides encouraging the application of the game to younger ages than determined in the research. In view of these considerations, the educational game is considered an AT for the blind and was assessed positively, as it permits access to information on psychoactive drugs in a playful way. The AT aroused the blind people’s will and desire to discover what it would be like to play this type of game. It was considered relevant for the teaching-learning process and is thus useful to promote these people’s health, constituting a new tool for nursing to use in its educational function.